MAKAN BEDULANG: SEBUAH TRADISI KULINER KOMUNAL DI BELITUNG, INDONESIA - Farah Levyta; Calvin Liu Hendra (Journal of Tourism Destination and Attraction, 2022)
When there is a declining in the number of tourist arrival, an authentic experience of food consumption could be an option to attract more visitors in a tourism attraction. Makan bedulang is one of the authentic traditions in Belitung regency which possibly attract people who are eager to encounter a new experience of food consumption within a group. The purpose of this study is to determine how local people and domestic tourists are exposed to the meaning of makan bedulang, while offering an added value for visitors to learn local virtues. Using qualitative methods with descriptive approach, this study utilizes interviews, literature studies, as well as questionnaires as an additional instrument. The result is that local people and visitors are aware of the meaning behind makan bedulang, but the information deserves more socialization to help domestic tourists find a more thorough local experience.